Pengaruh Gaya Kepemimpinan Transaksional dan Motivasi Terhadap Kinerja Karyawan di Hotel Vila Lumbung - Nugraha, Pande Kadek Oka Adi; Sulistyawati, Ni Luh Ketut Sri; Pramana, I Dewa Putu Hendri; Suprastayasa, I Gusti Ngurah Agung (Jurnal Ilmiah Pariwisata; Vol 28 No 1 (2023): Jurnal Ilmiah PariwisataDO - 10.30647/jip.v28i1.1661, 2023)
This study aims to determine the effect of transactional leadership style and motivation on employee performance at Hotel Vila Lumbung. Quantitative descriptive research is this type of research. The sampling technique in this study was saturated sampling, because the total population and number of samples in this study were the same, namely 38 employees of Hotel Vila Lumbung. Data collection techniques by distributing questionnaires with the analysis technique of multiple linear regression methods. The transactional leadership style in this study has a significant effect on employee performance at Hotel Vila Lumbung, because the transactional leadership style is used by Hotel Vila Lumbung to achieve goals efficiently, by motivating their subordinates to carry out tasks related to work results and giving awards. . Motivation in this study has a significant effect on employee performance at Hotel Vila Lumbung, because work motivation includes providing attractive career paths or promotions for employees which will affect high employee performance. Leaders at Hotel Vila Lumbung are expected to be able to guide, educate, protect and delight so that their employees can be happy and follow what their superiors order. Hotel Vila Lumbung needs to pay attention to work motivation so that work performance is higher. Keywords : Transactional Leadership Style, Motivation, Employee Performance